Guardianship Against Sexual Offenses: Exploring the Role of Gender in Intervention. (June 2016) - Cook, Alana; Reynald, Danielle
This article reviews the literature on bystander intervention with a view to establishing what we know about how guardians can be effective in preventing, disrupting, or reducing the severity of sexual offenses against women through intervention. Viewing bystanders as potential guardians, this review explores what is currently known about the presence of potential guardians at the scene of sexual offenses against women, and how these potential guardians respond to witnessing such events. Research shows that the likelihood and type of intervention by available guardians varies across situational contexts. Relatedly, trends in the characteristics of available and active guardians also reveal the importance of individual characteristics such as age, and most significantly gender, in affecting the willingness to intervene and perceptions of capability in intervening in various situational contexts. Results suggest that while men generally have greater confidence in their physical capability to intervene directly, women generally express a greater willingness to help and are more likely to intervene indirectly. The implications of these gendered bystander responses for sexual assault prevention are discussed.